The congressman [videorecording (DVD)] - Carbonara, David (Vision Films, 2016)
Maine Congressman Charlie Winship has had a bad day. After being caught on video failing to stand and recite the pledge of allegiance, he knocks out another House member, confronts his angry ex-wife, and faces denunciation by the media for attacking one of the most cherished patriotic symbols in America. As his life spirals out of control, Charlie embarks on a journey to a remote island in the Atlantic whose eccentric inhabitants are in the middle of a shooting war over their fishing grounds.